1996
DOI: 10.1177/152660289600300403
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Experience with a New Nitinol Self-Expanding Stent in Peripheral Arteries

Abstract: Purpose: To evaluate a new self-expanding nitinol coil stent in stenotic or occluded peripheral arteries. Methods: Seventy-three symptomatic patients (58 men; mean age 67 years) were treated with nitinol stents for lesions in the iliac artery (9 stenoses); superficial femoral artery (SFA) (39 stenoses, 6 occlusions); popliteal artery and tibioperoneal trunk (9 stenoses, 7 occlusions); and 3 bypass grafts. Mean diameter stenosis was 84.4% ± 9.9% (range 75% to 100%), and mean lesion length was 45 ± 23 mm (range … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 25 publications
2
14
0
Order By: Relevance
“…In addition, current stents made of stainless steel or other ferrous metals create artifacts under CT or MRI, limiting the capacity for noninvasive assessment. Nitinol is being increasingly used in vascular stenting [23,24]. The Endostent, due to its composition and design, may be able to solve each of the above-mentioned stent limitations.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, current stents made of stainless steel or other ferrous metals create artifacts under CT or MRI, limiting the capacity for noninvasive assessment. Nitinol is being increasingly used in vascular stenting [23,24]. The Endostent, due to its composition and design, may be able to solve each of the above-mentioned stent limitations.…”
Section: Discussionmentioning
confidence: 99%
“…2). Initial reports of stenting in the superficial femoral artery showed promising results with primary and secondary patency rates of 87-90% at 18 months [18]. However, subsequent studies demonstrated that exaggerated neo-intimal hyperplasia in the stented segment frequently leads to instent-restenosis and five randomized controlled trials failed to demonstrate a beneficial effect of SFA stenting using stainless-steel stents compared to plain balloon angioplasty [4,[19][20][21][22].…”
Section: Femoropopliteal Arteriesmentioning
confidence: 99%
“…Clinical outcomes are assessed at various (Duda et al, 2002;Sabeti et al, 2004;Duda et al, 2005;Sabeti et al, 2005;Duda et al, 2006) with a restenosis rate as low as 17.9% at eighteen months (Duda et al, 2005) and patency rates of more than 85% at 18 months (Henry et al, 1996). In contrast, angioplasty had restenosis rates of 40%-60% after one year (Dormandy and Rutherford, 2000) and stainless steel balloon-expandable stents had patency rates of 54% after one year (Gordon et al, 2001).…”
Section: Introductionmentioning
confidence: 97%